'If there is joy… I think it can work well': a qualitative study investigating relationship factors impacting HIV self-testing acceptability among pregnant women and male partners in Uganda. Issue 2 (17th February 2023) - Naughton, Brienna; Bulterys, Michelle A; Mugisha, Jackson; Mujugira, Andrew; Boyer, Jade; Celum, Connie; Weiner, Bryan; Sharma, Monisha
Abstract : Objectives: Secondary distribution of HIV self-test (HIVST) kits from pregnant women attending antenatal care (ANC) to their male partners is shown to increase HIV couples testing and disclosure, and is being scaled up in sub-Saharan Africa. Understanding couples-level barriers and facilitators influencing HIVST uptake is critical to designing strategies to optimise intervention coverage. Design: To investigate these couples-level barriers and facilitiators, we conducted focus group discussions and in-depth interviews. Transcripts were analysed thematically and the interdependence model of communal coping and health behaviour change was adapted to explore factors impacting HIVST acceptability. Setting: We recruited pregnant women attending two public ANC clinics in Kampala, Uganda, and male partners of pregnant women between April 2019 and February 2020. Participants: We conducted gender-stratified focus group discussions (N=14) and in-depth interviews (N=10) with pregnant women with and without HIV attending ANC, and male partners of pregnant women (N=122 participants). Intervention: We evaluated pregnant women's and male partners' perceptions of HIVST secondary distribution in Uganda, leveraging the interdependence model of communal coping and health behaviour change. Primary and secondary outcome measures: Key areas of focus included HIVST interest and acceptability, perspectives on HIV status disclosure to partners and gender roles. Results: Participants felt that predisposing factors, including trust, communication, fear of partner and infidelity, would influence women's decisions to deliver HIVST kits to partners, and subsequent communal coping behaviours such as couples HIV testing and disclosure. Pregnancy was described as a critical motivator for men's HIVST uptake, while HIV status of pregnant women was influential in couples' communal coping and health-enhancing behaviours. Generally, participants felt HIV-negative women would be more likely to deliver HIVST, while women with HIV would be more hesitant due to concerns about discovery of serodifference and relationship dissolution. Participants stressed the importance of counsellor availability throughout the process including guidance on how women should approach their partners regarding HIVST and post-test support in case of a positive test. Conclusions: HIV-negative women in relationships with positive predisposing factors may be most likely to deliver HIVST and leverage interdependent coping behaviours. Women with HIV or those in relationships with negative predisposing factors may benefit from targeted counselling and disclosure support before and after HIVST kit distribution. Results can help support policy guidelines for HIVST kit distribution.